Tinjauan Yuridis Tentang Tindak Pidana Penipuan dan Penggelapan Berkedok Investasi Online (Bitcoin) : (Studi Kasus Putusan PN Kupang Nomor 129/Pid.B/2021/PN. Kpg Jo Putusan PT Kupang Nomor 143/Pid/2021/PT Kpg Jo Putusan MA Nomor 422 K/Pid/2022) - Maria Graciana Erlan Jaja; Debi F. Ng. Fallo; Orpa G. Manuain (International Forum of Researchers and Lecturers, 2024)
Fraud through the internet or online-based fraud is a crime that is rife today. The increasing use of the internet turns out to open up greater opportunities for fraudsters to get money or profit from the internet. Transact in online investment activities using exchange in the form of electronic money (bitcoin). With this virtual money, now business transactions can be carried out without involving intermediaries such as banks. The main problem in this study is what is the form of fraud and embezzlement in online investment (BITCOIN) based on Kupang District Court Decision Number 129/Pid.B/2021/PN. Kpg Jo Kupang High Court Decision Number 143/Pid/2021/PT Kpg Jo Supreme Court Decision Number 422 K/Pid/2022 and whether the court decision against fraud and embezzlement under the guise of online investment (BITCOIN) is fair to the victim. This research is a normative legal research that examines based on existing decisions, laws and regulations, legal theories and opinions of scholars. The results of this study show that (1) there are two forms of criminal acts that researchers found in the verdict, namely fraud and embezzlement. (2) the aspect of justice contained in the decision that it is not fair to the victim based on the laws and regulations and criminal sanctions given to the accused. Therefore, suggestions for the results of this study are (1) It is recommended that local governments that have duties and responsibilities in solving these problems can pay attention to the application of criminal sanctions.